2010
DOI: 10.1177/1099636209359843
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanics of Materials/Fracture Mechanics Analysis of Core Shear Failure in Foam Core Composite Sandwich Beams

Abstract: An elementary laminated beam theory and linear elastic fracture mechanics have been used to analyze initial core shear failure and corresponding initial crack sizes in foam core sandwich beams. The model is not intended for application to crack growth and kinking, which are observed in experiments. Predictions from the model were compared with previous experimental results from four-point bending tests of polymethacrylimide foam core sandwich beams having either unidirectional carbon/epoxy face sheets or woven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Influence of setup-induced stress concentrations on results in shear tests is often encountered and reported. 36,37 From Figure 6B, we can observe a reduction of the experimental scatter in the G modulus with similar mean values between the control specimens and the T cycled specimens and an increase in the modulus for the thermal and mechanically cycled samples. This indicates that the mechanical cycles have a strain hardening effect on the foam.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Influence of setup-induced stress concentrations on results in shear tests is often encountered and reported. 36,37 From Figure 6B, we can observe a reduction of the experimental scatter in the G modulus with similar mean values between the control specimens and the T cycled specimens and an increase in the modulus for the thermal and mechanically cycled samples. This indicates that the mechanical cycles have a strain hardening effect on the foam.…”
Section: Discussionsupporting
confidence: 52%
“…Previous experimental studies indicate that this is the most common crack propagation mode in foam sandwich structures. 37,42 The consistent distance between cracks indicate that the foam experiences strain localizations in the axial direction, displaced by approximately 2-cm intervals, which are the main driver for the crack nucleation. Pre-existing voids or other defects would produce cracks located randomly.…”
Section: Discussionmentioning
confidence: 96%
“…The most common failure mechanism seen in composite sandwich structures in both static and fatigue flexural loading is core shear failure (Daniel & Abot, 2000), (Manalo, Aravinthan, Karunasena, & Islam, 2010), , (Gibson, 2011). Core shear failure is an undesirable failure mechanism when trying to investigate the face sheet and novel measures may be required to avoid core shear failure (Daniel & Abot, 2000).…”
Section: Sandwich Structuresmentioning
confidence: 99%
“…Therefore, flexural loadings have been extensively used in the literature in order to determine the core shear response [20,30,43,44,50,68,75,77,[85][86][87][88][89][90][91][92][93][94][95]. Therefore, flexural loadings have been extensively used in the literature in order to determine the core shear response [20,30,43,44,50,68,75,77,[85][86][87][88][89][90][91][92][93][94][95].…”
Section: Sandwich Bending Testsmentioning
confidence: 99%
“…Gibson [93], for instance, showed that for a PMI foam core, stiffer face sheets minimize stress concentrations in the core at the loading points and eventually cause the initial cracks to begin at the middle surface of the beam, whereas less stiff face sheets lead to core shear cracks initiating near the loading points (Figure 8.23). Gibson [93], for instance, showed that for a PMI foam core, stiffer face sheets minimize stress concentrations in the core at the loading points and eventually cause the initial cracks to begin at the middle surface of the beam, whereas less stiff face sheets lead to core shear cracks initiating near the loading points (Figure 8.23).…”
Section: Figure 818mentioning
confidence: 99%